Bureaucracy Communication and Government Organizational Culture - Khomsahrial Romli (UBL, 2013)
In general the function ofcommunication is toachieve thesense one to another, to build trust, to coordinateactions, to planstrategies, to perform division of labor, to perform a groupactivity, and to share the same sense. As thecommunication of government bureaucracy tasks are to serve, to regulate, to supervise, and to gain the relationshipbetween the governmentand thesociety, just imaginewhen thegovernment bureaucracydoes notinterpretthe importance ofcommunication, of course,the service process, the regulation, the supervision as well as the relationshipbetween the governmentand the societywill not run. In the end there come problems ofbothtrivialanddue toalack ofcommunicationwithin thegovernment bureaucracy. This makes the changes in the organizational culture in the government on the one hand can improve performance, but on the other hand can also fail if not properly maintained and prepared. However, what to watch is to know when the right time to make a change organizational culture is. The change in organizational culture is required in case if there is an un-avoided development in the environment. On the other hand, the changes become the internal need of the organization; it is perceived as a necessity. It is also required an understanding of how to have proper process to run the organizational change and to know what obstacles might be encountered. Errors can result in the emergence of resistance and failure in the attempt to change the organizational culture.